Inflammatory bowel disease detection and monitoring by measuring biomarkers in non‐invasively collected colorectal mucus. Issue 5 (27th April 2017) - Loktionov, Alexandre; Chhaya, Vivek; Bandaletova, Tatiana; Poullis, Andrew
Abstract: Background and Aim: Non‐invasive detection and monitoring of inflammatory bowel disease (IBD) is an important clinical challenge. Stool calprotectin is the most popular among available options, but the necessity of stool collection limits its acceptability. This study aimed to evaluate biomarker measurement in non‐invasively collected colorectal mucus as a new tool for IBD detection and activity monitoring. Methods: Calprotectin, eosinophil‐derived neurotoxin (EDN), and protein S100A12 were measured in colorectal mucus self‐collected following defecation by 58 patients with IBD (before therapy), 50 patients with irritable bowel syndrome, and 33 healthy volunteers. Patients with IBD also collected samples at days 10, 20, and 30 of treatment for disease activity monitoring. Results: Protein biomarker levels were significantly ( P < 0.001) higher in IBD patients than in irritable bowel syndrome and control groups. Calprotectin and EDN effectively detected IBD with a respective sensitivity and specificity of 0.76 and 0.92 for calprotectin and 0.83 and 0.94 for EDN. S100A12 was less sensitive. Calprotectin and EDN results were combined in a new test (CALEDN) that had a sensitivity of 0.91 and a specificity of 0.89. Repeated biomarker measurement during IBD treatment demonstrated a steady decline of calprotectin and EDN levels as well as CALEDN values in patients responding to applied therapy and lack of this pattern in non‐responders. Conclusions: Measuring calprotectin and EDN in non‐invasively collected colorectal mucus presents a simple and efficient method for IBD detection and monitoring. Excellent performance of EDN for this purpose is reported for the first time. Combining calprotectin and EDN in one test improves IBD detection sensitivity.